2008
DOI: 10.1667/rr1296.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Antioxidant Supplementation on the Development of Malignant Lymphoma and Other Neoplastic Lesions in Mice Exposed to Proton or Iron-Ion Radiation

Abstract: Malignancy is considered to be a particular risk associated with exposure to the types of ionizing radiation encountered during extended space flight. In the present study, two dietary preparations were evaluated for their ability to prevent carcinogenesis in CBA mice exposed to different forms of space radiation: protons and highly energetic heavy particles (HZE particles). One preparation contained a mixture of antioxidant agents. The other contained the soybean-derived Bowman-Birk protease inhibitor (BBI), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…As reported previously, there were no statistically significant differences in the survival of the irradiated animals (protons or iron ions) on the antioxidant or BBIC diets compared to the survival of irradiated animals maintained on the control diet (18). Therefore, there would not have been a bias in the cataract analyses resulting from the date the animals were killed.…”
Section: Lens Collection Isolation and Fixationsupporting
confidence: 50%
See 3 more Smart Citations
“…As reported previously, there were no statistically significant differences in the survival of the irradiated animals (protons or iron ions) on the antioxidant or BBIC diets compared to the survival of irradiated animals maintained on the control diet (18). Therefore, there would not have been a bias in the cataract analyses resulting from the date the animals were killed.…”
Section: Lens Collection Isolation and Fixationsupporting
confidence: 50%
“…The animals evaluated in this study were the same animals evaluated for other end points in a previously reported carcinogenesis study. The survival curves and other data concerning these animals are described in this earlier report (18).…”
Section: Animal Handling Dietary Supplementation and Radiation Exposurementioning
confidence: 96%
See 2 more Smart Citations
“…13 These data suggest that the AOX diet had the potential to block cell death through the mitochondrial deathinducing pathway. Interestingly, the same mixture of dietary antioxidants also prevented neoplastic transformation and the development of malignancies in mice following PR, 14 suggesting that dietary antioxidant supplementation could prevent both short-and long-term side-effects that are of concern following radiation treatment.…”
Section: Resultsmentioning
confidence: 99%